A species-specific triplex PCR assay for authentication of Galli Gigerii Endothelium Corneum. Issue 3 (4th March 2021) - Zhang, Yuli; Li, Juan; Yang, Shiqing; Xu, Chao; Gblinwon, Roselyn Tehzee; Hu, Jianhui; Sun, Xiaoxiang; Xia, Guohua; Yang, Huan; Shen, Yuping
Abstract: A triplex PCR assay was developed to identify animal species and adulteration of a natural medicine Galli Gigerii Endothelium Corneum (GGEC). Three species-specific primer sets were designed according to the difference in mitochondrial genome of Gallus gallus domesticus, Anas platyrhynchos and Anser anse . The PCR conditions were optimized and the assay was well validated for high specificity and sensitivity (1 mg/μL). Especially, when artificial adulterants made from the mixture of three species were analyzed, the assay has still exhibited strong capability of differentiation. By using this developed method, two batches out of fourteen commercial GGEC products were identified to be adulterated by Anser anse . The newly proposed assay showed sufficient merits as a regular tool for the identification of counterfeits or adulterants of GGEC product for their pulverized and processed form, and even Chinese patent medicines composed of these species.